$l_2$-Stability of Difference Models for Hyperbolic Initial Boundary Value Problems (Journal of Computational Mathematics, 1990)
It is showed that, for many commonly used difference models on hyperbolic initial boundary value problems, the necessary and sufficient condition for GKS-stability is a necessary condition for $l_2$-stability.